Parents' Experiences of Caring for Children with Cancer in the Early Diagnosis Phase: A Qualitative Study - Susi Roida Simanjuntak; Maria Lupita Nena Meo; Christha Zenithy Tamburian (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Background: Childhood cancer is a traumatic experience that significantly affects parents' lives, particularly during the early diagnosis phase, when parents must adapt to complex medical information, invasive procedures, and profound uncertainty within a short period of time. Studies exploring parents' experiences during this critical phase, particularly within the cultural context of North Sulawesi, remain very limited. Objective: This study aimed to explore parents' experiences in caring for children with cancer during the early diagnosis phase in North Sulawesi. Methods: This study used a qualitative descriptive design. Twelve mothers of children diagnosed with cancer were recruited through purposive sampling. Data were collected through in-depth interviews and analyzed using content analysis. Results: Three main themes emerged from the data: (1) Health Service Navigation, describing mothers' health-seeking behaviors, including the use of alternative therapies, utilization of health services, and circular treatment-seeking patterns; (2) Dynamics of Psychological Response, encompassing feelings of helplessness, negative emotions, self-blame, and anticipation of the possible diagnosis; and (3) Challenges, including difficulty understanding medical information, caregiving burden, and social stigma. Conclusion: The early diagnosis phase represents a psychologically demanding period for mothers of children with cancer, marked by uncertainty, emotional distress, and multidimensional caregiving burdens. These findings highlight the urgent need for early psychosocial support, health education, and culturally sensitive interventions from healthcare professionals to assist parents from the point of diagnosis onward, particularly in the North Sulawesi context.